1997
DOI: 10.1038/nm1097-1160
|View full text |Cite
|
Sign up to set email alerts
|

The role of CCR5 and CCR2 polymorphisms in HIV-1 transmission and disease progression

Abstract: Entry of human immunodeficiency virus type 1 (HIV-1) into target cells requires both CD4 (ref. 1, 2) and one of a growing number of G-protein-coupled seven-transmembrane receptors. Viruses predominantly use one, or occasionally both, of the major co-receptors CCR5 or CXCR4, although other receptors, including CCR2B and CCR3, function as minor co-receptors. CCR3 appears critical in central nervous system infection. A 32-base pair inactivating deletion in CCR5 (delta 32) common to Northern European populations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
3
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(145 citation statements)
references
References 27 publications
5
132
3
1
Order By: Relevance
“…Other studies have shown correlations between disease progression and the CCR2-64 I/V amino acid substitution and between CCR5 promoter haplotype/haplotype combinations (diplotype) [10,19,[23][24][25][26][27][28]. We were unable to demonstrate any relationship between these diplotypes and the in vitro phenotype; however, these additional analyses may have been limited by the small numbers of individuals in the diplotype in vitro phenotype categories observed in this study.…”
Section: Resultscontrasting
confidence: 66%
“…Other studies have shown correlations between disease progression and the CCR2-64 I/V amino acid substitution and between CCR5 promoter haplotype/haplotype combinations (diplotype) [10,19,[23][24][25][26][27][28]. We were unable to demonstrate any relationship between these diplotypes and the in vitro phenotype; however, these additional analyses may have been limited by the small numbers of individuals in the diplotype in vitro phenotype categories observed in this study.…”
Section: Resultscontrasting
confidence: 66%
“…[156][157][158] Individuals homozygous for CCR5D32 are resistant to HIV-1 infection, whereas the disease progresses slowly in individuals who are heterozygous for this mutation. [159][160][161] Other studies have shown that the proportion of T cells expressing CCR5 differs greatly between individuals and increases chronically in HIV-infected individuals during disease progression, 162,163 and others have shown that the cell surface density of CCR5 correlates positively with disease progression. 164,165 It has been also reported that T-cell depletion in peripheral blood during primary infection was related to T cells expressing CCR5.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%
“…Although there is no evidence for a strong protective effect in heterozygotes (Dean et al, 1996;Huang et al, 1996;Michael et al, 1997), a modest reduction in HIV incidence has been reported (Samson et al, 1996b). Also, the observation that cohorts of long-term survivors are enriched for CCR5∆32 heterozygotes suggests the existence of some protection against the AIDS progression (Dean et al, 1996;Michael et al, 1997).…”
Section: Introductionmentioning
confidence: 99%